Perpaduan Bali dan Jazz dalam Teknik Jazli, Tari Studi dalam Kontemporer - Putra, Putu Parama Kesawa Ananda; Sudibya, I Gusti Ngurah; Satyani, Ida Ayu Wayan Arya (Jurnal IGEL : Journal Of Dance, 2022)
The Blend of Bali and Jazz in Jazli Techniques, Dance Studies in Contemporary Jazli's dance work is a contemporary dance whose idea departs from the creator's personal experience. The experience of studying Jazz dance and the love of Balinese dance made the creators want to raise the acculturation of motion as the theme of the work. Through this dance work, the creator wants to convey the creator's pride in Balinese dance which is very flexible, so that it can be combined with Jazz dance originating from the West. This work aims to offer a new artistic creativity at the Indonesian Institute of the Arts Denpasar, especially in the Dance Study Program in completing the final project. The study dance type was chosen to combine Jazz dance techniques and Balinese dance techniques, so as to find new movement techniques. The creator uses Jacqueline Smith's method as the basis for building Jazli dance works. This method is divided into four stages, called the construction method I, II, III, and IV. In addition to the combination of movement techniques, in the process of his work there is also a combination of music and fashion to represent elements of Jazz and Bali. The form of presentation of Jazli dance works is a group of seven dancers, three male dancers and four female dancers. Jazli's movement technique is the result of the discovery in this dance work. Jazli's movement technique is the creator's reflection on the dance techniques he has studied. The creator hopes that Jazli's dance works can be used as inspiration for the younger generation, and Jazli's movement techniques can develop in Bali. Keywords: Contemporary, Experience, Jazli, Acculturation